Size, sex and seasonal dynamics in the dietary composition of Brycinus nurse (Pisces: Characidae), from Asa reservoir, Ilorin, Nigeria - Saliu, J K (Revista de Biología Tropical, 2002)
Specimens of the characid Brycinus nurse (N = 980) were collected in Asa reservoir, Nigeria, from November 1991 to October 1993. The diet was analyzed from stomach contents using the frequency of occurrence, numerical and gravimetric methods. Fish sex affected occurrence, number and weight of food items. The relative importance index (RI) indicates that diet varied seasonally. There was also a noticeable switch from insectivorous habits in small fish (less than 18 cm) to herbivorous feeding habits in larger fish. The ability of the fish to evolve trophic strategies that ensure optimum foraging despite seasonal changes can account for its success in the lake.